Promoting health through music in motherhood: perceptions of pregnant and puerperal women - Marquesini, Tainá de Miranda; de Souza, Jeane Barros; Zilio, Iasmin Cristina; Heidemann, Ivonete Terezinha Schulter Buss; Rosa, Odila Migliorini; Barbosa, Simone dos Santos Pereira [UNESP] (Universidade de Estado do Rio de Janeiro, 2023)
Objective: to understand the perceptions of pregnant and postpartum women about the use of music as a care technology for health promotion. Method: qualitative research, based on the assumptions of health promotion, carried out with seven pregnant women and eight postpartum women admitted to the maternity ward of a public hospital in Santa Catarina. Semi-structured interviews were carried out between September 2021 and February 2022, after approval by the Research Ethics Committee. Data were analyzed using content analysis. Results: music in the maternity ward reduces stress and sadness. In addition, it provides distraction, joy, animation, recall of memories, a special moment, gratitude and tranquility for hospitalized women and their babies. Final considerations: for pregnant and postpartum women, music has the ability to promote health, being a care technology that should be present in all maternity hospitals in Brazil.
Promoviendo la salud a través de la música en la maternidad: percepciones de las mujeres embarazadas y puérperas
Promovendo saúde por meio da música na maternidade: percepções de gestantes e puérperas
Keywords: Complementary Therapies; Health Promotion; Hospitals, Maternity; Music; Music Therapy